2019
DOI: 10.1002/adfm.201901722
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Fe(III)@WS2‐PVP Nanocapsules for Redox Reaction and TME‐Enhanced Nanocatalytic, Photothermal, and Chemotherapy

Abstract: In this study, biocompatible Fe(III) species‐WS2‐polyvinylpyrrolidone (Fe(III) @ WS2‐PVP) nanocapsules with enhanced biodegradability and doxorubicin (DOX) loading capacity are one‐pot synthesized. In this nanocapsule, there exists a redox reaction between Fe(III) species and WS2 to form Fe2+ and WO42−. The formed Fe2+ could be oxidized to Fe3+, which reacts with Fe(III) @ WS2‐PVP again to continuously produce Fe2+ and WO42−. Such a repeated endogenous redox reaction leads to an enhanced biodegradation and DOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 27 publications
0
80
0
Order By: Relevance
“…Because the nanoplatform is specific to the tumor microenvironment, the efficiency of the combination therapy can be enhanced. 67 Despite the fact that inorganic nanoparticle combinational therapies have favorable properties, they still need further investigation. Recent studies in this review demonstrated the application of nanomaterials for such purposes using in vitro and in vivo experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the nanoplatform is specific to the tumor microenvironment, the efficiency of the combination therapy can be enhanced. 67 Despite the fact that inorganic nanoparticle combinational therapies have favorable properties, they still need further investigation. Recent studies in this review demonstrated the application of nanomaterials for such purposes using in vitro and in vivo experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Although this review presents some promise aspects for nanoparticles to simultaneously treat cancer cells and bacteria, much more work is needed especially on the antibacterial side. Furthermore, it is also possible to combine PTT with other cancer treatments (such as chemodynamic therapy 67 and nanoCRISPR 68 ) together to promote the synergistic effects necessary for treating cancer. Inorganic nanomaterials have demonstrated exceptional accomplishments in biomedical research.…”
Section: Resultsmentioning
confidence: 99%
“…found that PEG‐SH modification could prolong circulation half‐life and improve tumor accumulation of Pd nanosheets, and Pd nanosheets with PEG‐SH modification dispersed better than those with PEG‐NH 2 , because of the stronger coordination interaction between the thiol group and Pd nanosheets. Other biocompatible polymers such as polyvinylpyrrolidone (PVP), polydopamine (PDA), and biological molecules such as bovine serum albumin (BSA) are also applied in the modification of 2D nanomaterials . Moreover, surface modification can improve the chemical stability of 2D nanomaterials.…”
Section: Modification Of 2d Nanomaterialsmentioning
confidence: 99%
“…[9] Photothermal agents and photosensitizers play ac rucial role in converting NIR light irradiation into heat and reactive oxygen species (ROS)f or photothermal therapy (PTT) and photodynamic therapy (PDT), respectively. [10] Moreover, they can serve as molecular transducers to transform NIR light into other forms of cues for regulation of biological events (for example,n eural activity, [11] gene transcription, [12] and enzymatic activity [13] )aswell as remote activation of prodrugs through uncaging certain photolabile moieties. [14] However, NIR light has been barely exploited as the exogenous stimulus for the in situ activation of the pharmaceutical effect of immunostimulatory agents for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%